Molecular sonification for molecule to music information transfer. (21st March 2023) - Mahjour, Babak; Bench, Jordan; Zhang, Rui; Frazier, Jared; Cernak, Tim
Abstract : Organic chemical structures can be encoded as a simple musical phrase. Abstract : Organic chemical structures encode information about a molecule's atom and bond arrangement. The most established way to encode a molecular structure is through line drawing, although other representations based on graphs, strings, one-hot encoded labels, or fingerprint arrays are critical to the computational study of molecules. Here we show that music is a highly dimensional information storage medium that can be used to encode molecular structure. The resultant method allows a molecular structure to be heard as a musical composition, where the key of the music is based on the molecular properties and the melody is based on the atom and bond arrangement. This allows for a molecular generation approach that leverages modern artificial intelligence tactics for music generation.